PENINGKATAN KAPASITAS PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA SUNGAI PINANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Amri, Pahmi (UIR PRESS, 2019)
Village government is the administration of government affairs and the interests of local communities in the NKRI government system (Law Number 6 of 2014 concerning Villages Article 1 Paragraph (2)). The village head as the organizer of the village government is directly elected by the community through the election of the village head (Law Number 6 of 2014 Article 34 paragraph 1). The village head in village administration is assisted by village officials, namely the village secretary and other village officials.